REKAYASA STRUKTUR AKSEPTOR PADA ZAT WARNA ORGANIK TIPE D- π -A DENGAN KERANGKA TIOFEN - Imelda Imelda (UIR Press, 2020)
This research study about tiofen based organic dyes with D-π-A type as sensitizer on DSSC. The dyes were varied with the acceptor chain and were given names of dyes 1 to 10. The dye with the smallest band gap was added with the electron withdrawing and donating groups. The computational study used the hyperchem package with the AM1 calculation method. The result showed that dye 8 has the smallest band gap is 4,9 eV and dipole moment is 9,3 D. The effect of adding Cl as an electron withrawing group (EWG) can reduce the band gap value to 4,7 eV. The conclusions are that dye 8 is more potential as sensitizer on DSSC and the addition of Cl as EWG can improve the light harvesting efficiency.